ANALYSIS OF MICROPLASTIC ABUNDANCE IN JERBUNG SHRIMP (FENNEROPENAEUS MERGUIENSIS) IN WIND SEA WATER, PASURUAN EAST JAVA PROVINCE - Meishela Dwi Lawidya; Riza Rahman Hakim; Hariyadi Hariyadi (Universitas Muhammadiyah Malang, 2025)
Plastic production worldwide has increased the development of synthetic polymers in the mid-20th century. When disposed of in the marine environment, plastic can harm organisms in the sea. The plastic degradation process is very slow, and thus microplastic has the potential to last for a very long period of time in the marine environment (Hidalgo, et al , 2012). This can threaten organisms in the waters to consume microplastic continuously. The purpose of this study is to determine the captured shrimp in the waters are microplastic contaminated and to find out what type of microplastic is found. Shrimp sampling is done for two months, located in the Lekok Sea Waters, Pasuruan Regency, East Java. Shrimp samples that have been taken are then analyzed in the fisheries laboratory by taking shrimp intestines and shrimp meat and then adding 10% KOH at a ratio of 1: 3 and roasted using a temperature of 60˚C for 24 hours for the destruction process. Based on microplastic analysis of the shrimp, it was found that the largest abundance of microplastic was dominated by microplastic fiber types compared to other types such as fragments and films. The abundance results show that at station 1 the average is 1 - 43 particles / gram, station 2 the average abundance value of microplastic is 2 - 31 particles / gram, station 3 the average abundance is 2 particles / gram - 31 particles / gram with very diverse sizes.